Effects of Lattice Temperature on the Various Elements of Heat Sources in Silicon Carbide Polymers (6H-SiC and 3C-SiC) Semiconductor Laser - Marjani, Saeid; Marjani, Hamid (Asian Journal of Chemistry, 2012)
In present paper, the various elements of heat sources within a silicon carbide polymers (6H-SiC and 3C-SiC) semiconductor laser device were analyzed upon the increment of lattice temperature. The device employs 3C-SiC quantum well, which is sandwiched between two layers of 6H-SiC as cladding regions that can be interpreted in terms of a type-II heterostructure character and a built-in electric field due to the pyroelectricity of 6H using a numerical simulator. The thermal resistance used to model the electrical contacts causes an approximate temperature rise by 29.3 K above the ambient temperature (300 K) at a bias of 2.5 V and a 17.094 % decrease from 1.3432e10 W/cm3 to 1.1136e10 W/cm3 in the total heat power is observed with temperature increment.